Industrial design A-Z - Fiell, Charlotte; Fiell, Peter (Taschen, 2003)
For over 200 years, the products or mechanized industrial production have shaped our material culture, influenced world economies and affected the quality of our environment and daily lives. From consumer goods and packaging to transportation systems and production equipment, industrial products encompass an extraordinary range of functions, techniques, attitudes, ideas and values and are a means through which we experience and perceive the world around us.